Combining organic and conservation agriculture to restore biodiversity? Insights from innovative farms in Belgium and their impacts on carabids and spiders - Boeraeve, Fanny; Vialatte, Aude; Sirami, Clélia; Caro, Gaël; Thenard, Jodie; Francis, Frédéric; Dufrêne, Marc (Frontiers in Sustainable Food Systems, 2022)
Conservation and organic agriculture are two alternative crop management strategies associated with environmental impact reduction, leading theoretically to more biodiversity and higher ecological functioning, underpinning better ecosystem service delivery. The combination of these two farming strategies is increasingly seen as an opportunity to mitigate shortcomings of each of them taken individually. However, combining organic and conservation agriculture is undeniably challenging, since it leaves no curative option (neither synthetic pesticides nor soil plowing) for pest control (phytophagous, pathogens, and weeds). Hence, the latter must be ensured by effective restoration of predatory communities. The present research investigated the potential of combining organic and conservation agriculture to support two major ground-dwelling natural enemy communities: carabids and spiders. We used pitfall traps to sample these two communities in paired adjacent cereal fields conducted under organic-conservation (OC) and conventional (CV) agriculture in Belgium. Community assemblages were significantly different across system types, both in terms of species diversity and functional trait diversity. OC parcels showed higher alpha and beta species diversities for both carabids and spiders and species composition differed between OC and CV parcels. OC systems were associated with higher variation of species assemblages among parcels than CV systems Functional traits also differed across system types for both groups. We found more herbivorous and granivore carabids in OC parcels, and more predator species in CV parcels. We found larger spiders, more hunting spiders and more wetland spiders in OC parcels, whereas we found more web weavers and more forest spiders in CV ones. Functional diversity was higher in OC parcels for carabids, but not for spiders. In brief, OC parcels supported more diverse communities, both taxonomically and functionally. These outcomes show that OC systems are promising systems to support these natural enemy communities. Further studies should assess whether combining organic and conservation agricultural enables sufficient pest control levels to achieve high levels of food production and farmers income.